A Novel iRFP-Incorporated in vivo Murine Atherosclerosis Imaging System - Kaushalya Kulathunga (Nature Portfolio, 2018)
Abstract By using near-infrared fluorescent protein (iRFP)-expressing hematopoietic cells, we established a novel, quantitative, in vivo, noninvasive atherosclerosis imaging system. This murine atherosclerosis imaging approach targets macrophages expressing iRFP in plaques. Low-density lipoprotein receptor-deficient (LDLR −/− ) mice transplanted with beta-actin promoter-derived iRFP transgenic (TG) mouse bone marrow (BM) cells (iRFP → LDLR −/− ) were used. Atherosclerosis was induced by a nonfluorescent 1.25% cholesterol diet (HCD). Atherosclerosis was compared among the three differently induced mouse groups. iRFP → LDLR −/− mice fed a normal diet (ND) and LDLR −/− mice transplanted with wild-type (WT) BM cells were used as controls. The in vivo imaging system (IVIS) detected an enhanced iRFP signal in the thoracic aorta of HCD-fed iRFP → LDLR −/− mice, whereas iRFP signals were not observed in the control mice. Time-course imaging showed a gradual increase in the signal area, which was correlated with atherosclerotic plaque progression. Oil red O (ORO) staining of aortas and histological analysis of plaques confirmed that the detected signal was strictly emitted from plaque-positive areas of the aorta. Our new murine atherosclerosis imaging system can noninvasively image atherosclerotic plaques in the aorta and generate longitudinal data, validating the ability of the system to monitor lesion progression.